Delignification of banana stem waste in anaerobic conditions by using Bacillus cereus - Nur Husna, Baharuddin (2009)
Today, the productions of biodegradable plastics are crucial due to the environment problems that keep escalating caused by conventional plastics. Many efforts have been done to reduce the cost of biodegradable plastic including by using waste as raw material. Production of biodegradable plastics by microorganism needs carbon sources. Several ranges of microorganisms have been tested for their ability to degrade lignin in order to obtain cellulose content to be used as carbon source. In this study, the submerged fermentation in anaerobic conditions of banana stem waste using Bacillus cereus and the capability of Bacillus cereus to delignify banana stem waste in anaerobic conditions are investigated. This study was divided into three parts which are the revival of Bacillus cereus, growth curve determination of Bacillus cereus, and delignification fermentation and analysis of Bacillus cereus. Fermentation was carried out anaerobically in batch mode at 30 oC and 37 oC. The analysis was done in accordance to Klason method. Results showed that Bacillus cereus was able to survive for 48 hours in anaerobic conditions and it is able to degrade lignin from banana stem waste. The optimum temperature for Bacillus cereus to degrade lignin was at 30 oC with average percentage of lignin degradation of 13.33 %.-Author-